Evolution of renewable energy generation in EU27. A decomposition analysis. (May 2023) - Driha, Oana; Cascetta, Furio; Nardini, Sergio; Bianco, Vincenzo
Abstract: The present paper analyses the evolution of renewable energy generation in the European Union through a decomposition analysis based on the Index Decomposition Analysis together with the Logarithmic Mean Divisia Index within the EU27 between 2000 and 2020. A four factors decomposition approach is considered for decomposing the total RES generation and a five factors model is employed to decompose the carbon emissions. Furthermore, a focus on wind and solar photovoltaic generation is introduced through a four factors decomposition calculated in the period 2010–2020. The most influential factors affecting the RES generation trend in the period 2000–2020 are the RES share and energy efficiency wich determined an increase of 1841 TWh and a decrease of 635 TWh respectively. Variations of carbon emissions are mostly affected by the energy intensity, namely the amount of energy necessary to produce one unit of GDP, which determined a reduction of 1040 Mt. Through the decomposition analysis, the paper successfully identifies the specific drivers supporting RES development and controlling carbon emissions, thus adequate policy measures can be designed to reach planned targets. Highlights: LMDI methodology is used to study decomposition of RES generation in EU. Technical and socio-economic factors are highlighted by using 4 or 5 factors identity. Technical factors have the main impact on the increase in RES generation.